Cancer-Related Fatigue: Perception of Effort or Task Failure?. (January 2020) - Fernandez, Carlos; Firdous, Shagufta; Jehangir, Waqas; Behm, Bertrand; Mehta, Zankhana; Berger, Andrea; Davis, Mellar
Context: Patient's rating of perceived effort (RPE) is used to assess central fatigue. Cancer-related fatigue (CRF) is believed to be of central origin. The increased RPE with a motor task, such as the Finger-Tapping Test (FTT), can easily be measured in the clinical setting. Objectives: To correlate the FTT, RPE and the Brief Fatigue Inventory (BFI) rated fatigue severity in patients with cancer. Methods: Subjective fatigue was assessed in adult patients with cancer by the BFI. Participants performed a modified FTT with the index finger of the dominant hand: 15 seconds × 2, 30 seconds × 2, and 60 seconds × 2 with 1 minute of rest between each time trial. Rating of perceived effort at the end of task was measured by the Borg 10 scale. Exclusions: Brain metastasis, history of brain radiation, Parkinson disease, Huntington Chorea, multiple sclerosis, delirium, and depression. Pearson correlation coefficients were used to describe the relationships between BFI, FTT, and Borg 10 scale. Results: Thirty patients participated. Mean age was 56.2. Sixteen were females (53.3%). The mean BFI mean was 4.1, median 4.4. Tapping rate did not correlate with fatigue severity. The RPE correlated with the mean BFI: r s 0.438, P = .0155. These correlations persisted after adjustment for age. Conclusion: An increased RPE in the absence of task failure suggests that the origin of CRF is central. The performance of an FTT with RPE helps to improve our understanding of fatigue in the clinical setting.